ERG expression in BPH vs prostatic adenocarcinoma and its correlation with Gleason grade group - Qayyum, Mubina; Summayya Shawana; Beenish Hussain Nomani; Erum Khaliq; Nighat Jamal; Qayyum, Hafsa (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate immunohistochemical expression of erythroblast transformation-specific-related gene in prostate carcinoma and benign prostate hyperplasia, and its association with Gleason grade groups. Method: The retrospective, comparative, cross-sectional study was conducted from January to December 2022 at the Department of Histopathology, Pakistan Navy Ship Shifa Hospital, Karachi, and comprised prostate samples from January 2019 to January 2020. All tissue specimens were subjected to immunohistochemical staining with erythroblast transformation-specific-related gene. The expression of immunohistochemical and its association was determined in benign prostate hyperplasia and prostate carcinoma groups. Data was analysed using SPSS 23. Results: Of the 60 cases with mean age 72±7.4 years (range: 58-88 years), 33(55%) had prostate carcinoma and 27(45%) had benign prostate hyperplasia Of the prostatic carcinoma cases, 20(60.6%) showed positive nuclear staining, while 13(39.4%) showed no nuclear staining. Weak positive staining was observed in 3(9.1%), and moderate in 3(9.1%) cases. Strongly positive ERG expression was found in 14(42.4%) patients. The erythroblast transformation-specific-related gene was equally expressed in low and high Gleason grade groups of prostate carcinoma (p>0.05). All 27(100%) cases of benign prostate hyperplasia showed negative immunohistochemical expression for erythroblast transformation-specific-related gene. Conclusion: The erythroblast transformation-specific-related gene expression was found to be associated with prostate carcinoma compared to benign prostate hyperplasia cases, and could be used as a diagnostic tool for distinguishing between the two. Key Words: Prostate carcinoma, Benign prostatic hyperplasia, BPH, ERG protein, Immunohistochemistry.